HIV- und AIDS-Patienten auf der Intensivstation - Mandraka, Falitsa (Intensivmed Notfallmed, 2003)
The number of HIV-infected patients in Germany has increased steadily over time. This is due to the positive development of decreasing death rates and a nearly stable rate of new infections. This development is based on the improved prognosis for HIV/AIDS patients due to the introduction of highly active antiretroviral therapy (HAART) in 1996. Considering this, a new look at the HIV patient as a potential ICU candidate is necessary.    The most common referral for ICU therapy is respiratory failure, followed by neurological disorders. In rare cases, HAART-induced side-effects require therapy in the ICU.    Very few clinical trials directly compare the outcome of HIV-positive and HIV-negative patients, and most of these data were collected in the pre-HAART era. The ICU outcome does not correlate with HIV-genuine parameters, such as the CD4 cell counts. Thus, a HIV patient can benefit from ICU treatment.    Regarding HAART management, open questions still exist especially considering the mechanically ventilated patient. Actually only AZT (Retrovir®) is available as an i.v. formulation. Other antiretroviral medication can only be administered after grinding the tablets. The consequenses of the altered galenic composition with regard to efficacy and development of resistance has not been sufficiently studied. This also applies to risks and benefits of interrupted therapy versus a possibly inappropriate application of HAART.    In this survey we also describe possible interactions between HAART and sedative/antiepileptic/tuberculostatic etc. medication.    Finally special aspects of HIV exposure in the health care setting are discussed, including essential immediate measures after an injury. Current recommendations for post-exposure prophylaxis are given.